An evaluation of trimetazidine as a therapeutic intervention in a newly established ex vivo mouse model of acute heart failure - Breedt, Emilene S. (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.